An overview of electromagnetic band-gap integrated wearable antennas - Dahlan, Samsul Haimi; Zainal Abidin, Zuhairiah; Ashyap, Adel Yahya Isa; Abbasi, Muhammad Inam; Kamarudin, Muhammad Ramlee; A. Majid, Huda; Dahri, Muhammad Hashim; Jamaluddin, Mohd Haizal; Alomainy, Akram (Institute Of Electrical And Electronics Engineers Inc., 2020)
The recent advancement in the wireless technology has led to the advent of wearable antennas. These antennas are utilized for Wireless Body Area Networks (WBANs) purposes such as healthcare, military sportive activities and identification systems. Compared to conventional antennas, wearable antennas operate in an environment which is in highly near proximity to the curved human body. Therefore, the wearable /flexible antenna performance parameters, including reflection coefficient, bandwidth, directivity, gain, radiation characteristic, Specific Absorption Rate (SAR), and efficiency are anticipated to be influenced by the coupling and absorption by the human body tissues. In addition, an electromagnetic bandgap structure is introduced in the wearable /flexible antenna designs to enable and give a high degree of isolation from the human body which also decreases the SAR dramatically. This paper reviews the stateof-the-art wearable/flexible antennas integrated with the electromagnetic band-gap structure on flexible materials concentrating on single and dual-band designs. Besides, it also highlights the challenges and considerations for an appropriate wearable/flexible antenna.